PEGAWAI NEGERI SIPIL SEBAGAI WAKIL KEPALA DAERAH - Riris Katharina (Jurnal Politica, 2012)
Government’s proposal to appoint civil servants as deputies head of region in bill on Regional Government, which will amend Law no. 32 year 2004, is important to be discussed. This essay discusses the proposal by examining reasons revealed by the government and analyzing it by applying the perspective of administrative discipline and theories. The writer comes to the conclusion that the reasons are not quite rights so that the proposal cannot consequently be wholly justified. The writer founded that government’s officials who propose or support the notion still cannot disconnect between the position of deputies head of region as political appointees with their sources of recruitment, namely, the bureaucracy, which is identical with the government. This essay, therefore, suggests that source of recruitment or appointment shall be not only from the bureaucracy but also from political parties as long as the candidates have good capability to conduct their tasks and duties.